Evaluasi Kondisi Pohon Tumbang Hesperocyparis guadalupensis (S.Watson) Bartel dan Pavetta sp. di Kebun Raya Eka Karya Bali Berdasarkan Penilaian Visual dan Teknologi Tomografi - Komang Kartika Indi Swari; Dewa Ayu Intan Tirta Sari; Siti Fatimah Hanum; Ayyu Rahayu (Jurnal Ilmu Kehutanan, 2022)
The health of fallen tree collection especially which has not been assessed yet, has to be evaluated to understand its cause. This study aimed to see the health conditions of Cupressus guadalupensis and Pavetta sp. and the causes of fallen trees. The identification of tree health was done visually with a modified Tree Risk Assessment (TRA) form from the International Society of Arboriculture (ISA). Meanwhile, the internal examination used ArborSonic 3D Acoustic Tomograph. The tomogram results showed a hole in the tree trunk. The cause of the fallen trees was predicted due to structural damage with wind factors.